Effect of Financial Literacy on the Profitability of Small-Scale Enterprises in Rubaare Town Council Ntungamo District. - Tugumisirize, Fiona (Kabale University, 2024)
The study's main objective was to examine the effects of financial literacy on the profitability of small-scale enterprises in Rubaare Town Council. The study aimed to investigate the effect of financial knowledge, financial behavior, and financial attitude on the profitability of small-scale enterprises in Rubaare Town Council. The study adopted a descriptive research design to analyze the obtained primary data and to give a clear understanding of the research objectives. This research helped in observing the effects of financial knowledge, financial behavior, and financial attitude on the profitability of small-scale enterprises in Rubaare Town Council. The study involved samples drawn from employees, business owners, and CDOs. To achieve the objectives, the primary data was gathered by issuing a set of structured questionnaires to a sample population of 133 owners/managers of SSEs that have their own businesses in Rubaare Town Council. Descriptive statistics and inferential statistics were employed to analyze the effect of financial literacy on the profitability of SSEs. The finding suggests that most of the financial literacy such as financial knowledge, financial attitude, and financial behavior have positive and significant effects on the profitability of SSE owners in the Rubaare Town Council. The study concludes that financial knowledge has a necessary effect in translating into profits. It also concludes that good financial behavior contributes to the profitability of SSEs. Also, a positive attitude toward the future and social influences for the acquisition of skills translate into profits for small-scale enterprises. The study, therefore, recommended that financial education and training programs should have to be given by the government along with other institutions, to encourage the application of financial knowledge to activities of business owners. These programs should also be able to motivate and encourage positive attitudes toward the future orientation and growth of the businesses. The study also recommends that the informal sector should be encouraged to keep records of their transactions to prevent losses and miscalculations.